The challenge of the energy sector of Russia during the 2020 covid-19 pandemic through the example of the Republic of Tatarstan: Discussion on the change of open innovation in the energy sector - Anastasia Kulachinskaya; Irina G. Akhmetova; Varvara Y. Kulkova; Svetlana B. Ilyashenko (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Today the world economy is handling an economic crisis caused by the pandemic of a new coronavirus infection (COVID-19), announced by the WHO, as well as by fluctuations in the international energy market and by the development of "green energy". The crisis, named the "2020 crisis", is notable for the divergence of the sectoral dynamics of development, with a declining development trend in some industries and the rapid growth of others. The crisis is etymologically relevant to the energy sector, a sector which is important for the survival and specialization of the Russian Federation. This research is aimed at describing the status and highlighting the socioeconomic effects, constraints (economic and social risks), and "growth points" of the energy sector in the modern realities of the 2020 crisis. Methods. The method of in-depth interview was used. The need for studying expert opinion is based on the fundamental principles of implementation research, according to which the success of state sectoral policy depends on its perception and support by stakeholders. Top managers of energy enterprises acted as the experts (N = 10). The interviews were conducted in April 2020. The method of incremental approximation and coding (open and axial) were used for a high-quality discourse analysis. Results. The conducted study revealed divergence of sectoral dynamics of energy consumption, which is a translation of the immanent features of the 2020 crisis into the energy sector. The detected constraints are reserved development prerequisites of "green energy" and reduced investments in development programs. The potential "growth points" include intensified digitalization of the energy sector and the need for institutional changes in taxation in the energy sector, recognized by experts.
Keywords: 650; anti-crisis actions of companies; energy economy; state policy during the "2020 crisis"